Pengembangan Modul Penguatan Pendidikan Karakter Jujur Berbasis Kisah Nabi dan Rasul untuk Murid Fase B - Kafa Sakinah; Rudi Hartono; Wido Supraha (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The problem frequently encountered today is regarding morality, ethics, behavior, and character of students occurring in both educational institutions and family environments. Although character education has been promoted through various policies, in practice there are still many students who do not demonstrate honest behavior. This study aims to analyze the need for developing a character education strengthening module based on the stories of prophets and messengers for phase B students using the R&D (Research and Development) method with the ASSURE development model, which consists of six stages: (1) Analyze Learners (analyzing student characteristics), (2) State Objectives (determining learning objectives), (3) Select Methods, Media, and Materials, (4) Utilize Media and Materials, (5) Require Learner Participation, and (6) Evaluate and Revise. Data were collected through literature studies, interviews with educators, feasibility testing of the module with experts, and trials of the module with students and teachers. The results of the study show that the development of the character education strengthening module on honesty based on the stories of prophets for phase B students began with analyzing learners; in the first stage, the researcher analyzed the identification of students' needs in understanding the concept of honesty, including an analysis of the learning situation, analysis of general student character, and analysis of basic competencies. The second stage is to state objectives, where the researcher conducted an analysis of the curriculum used in the school. The third stage is to select methods, media, and materials. At this stage, the researcher selects the methods according to the students' learning styles in school. The fourth stage is to utilize media and materials, which involves the use of modules by both teachers and students. The fifth stage is to require learner participation, which involves the participation of students in learning activities. Finally, there is evaluate and revise, at this stage, which involves evaluating and revising the modules. The results of this research showed that the validation from material experts was 90%, language experts 77.08%, and design experts 97.32%, with a percentage value in the 'Very Feasible' category. Thus, the character education strengthening module on honesty is very feasible to use. The conclusion of this research is that the honesty character education strengthening module based on the stories of prophets and messengers can serve as an effective learning medium in instilling the value of honesty in Phase B students. The recommendations from this study include further development of modules with more interactive delivery methods and integration with digital technology to enhance the appeal and effectiveness of learning.